Tháng Ba 1, 2024

Rút gọn \(Q.\) A \(Q = \frac{{\sqrt x }}{{\sqrt x – 2}}\) B \(Q = \frac{{\sqrt x }}{{\sqrt x + 2}}\) C \(Q = \frac{{\sqrt x + 2}}{{\sqrt x – 2}}\) D \(Q = \frac{{\sqrt x – 2}}{{\sqrt x + 2}}\)

Rút gọn \(Q.\)

A \(Q = \frac{{\sqrt x }}{{\sqrt x – 2}}\)

B \(Q = \frac{{\sqrt x }}{{\sqrt x + 2}}\)

C \(Q = \frac{{\sqrt x + 2}}{{\sqrt x – 2}}\)

D \(Q = \frac{{\sqrt x – 2}}{{\sqrt x + 2}}\)

Hướng dẫn Chọn đáp án là: A

Phương pháp giải:

Quy đồng mẫu, biến đổi và rút gọn biểu thức.

Lời giải chi tiết:

Điều kiện: \(x > 0,\,\,\,x \ne 4.\)

\(\begin{array}{l}Q = \frac{{\sqrt x – 1}}{{\sqrt x + 2}} + \frac{{5\sqrt x – 2}}{{x – 4}} = \frac{{\sqrt x – 1}}{{\sqrt x + 2}} + \frac{{5\sqrt x – 2}}{{\left( {\sqrt x + 2} \right)\left( {\sqrt x – 2} \right)}}\\\,\,\,\,\, = \frac{{\left( {\sqrt x – 1} \right)\left( {\sqrt x – 2} \right) + 5\sqrt x – 2}}{{\left( {\sqrt x + 2} \right)\left( {\sqrt x – 2} \right)}} = \frac{{x – 3\sqrt x + 2 + 5\sqrt x – 2}}{{\left( {\sqrt x + 2} \right)\left( {\sqrt x – 2} \right)}}\\\,\,\,\,\, = \frac{{x + 2\sqrt x }}{{\left( {\sqrt x + 2} \right)\left( {\sqrt x – 2} \right)}} = \frac{{\sqrt x \left( {\sqrt x + 2} \right)}}{{\left( {\sqrt x + 2} \right)\left( {\sqrt x – 2} \right)}} = \frac{{\sqrt x }}{{\sqrt x – 2}}.\end{array}\)

Chọn A.